Efecto de las dietas de harina de alverja, maca y soya en el desarrollo de núcleos de Apis mellifera L. - Medina Vásquez, Bianca Alejandrina Stefany (2018)
The objective of this work was to determine the effect of pea, maca and soy flour diets on the growth of Apis mellifera core. A completely randomized experimental design was used, with protein diets in 12 core-holders with 4 treatments and 3 repetitions; the first without artificial diet, the other treatments received diets of pea flour, maca and soy; the effect was evaluated every 7 days in brooth population, adult population and weight gain of the colony in 42 days. ANOVA and comparison of Tukey's means were performed. It was found that the population of brooth was similar between 28.73 and 31 occupied cells, with respect to the adult bees population and the weight of the colony, which was fed with soy flour diet is estimated 7063 adult bees and an increase 3680 g respectively. Therefore, the soy flour diet increases the adult bees population and the weight of the A. mellifera bee colony compared to the control treatments, pea and maca flour diets.